The Effect of Deep Breathing Relaxation and Imagery Distraction on Pain Intensity Using the Visual Analog Scale (VAS) in CAPD Patients After Double-Lumen Catheter Insertion - Shafa Puspita Maharani; Chairul Huda Al Husna (Asosiasi Dosen Muda Indonesia, 2026)
Introduction: Patients with Continuous Ambulatory Peritoneal Dialysis (CAPD) undergoing double lumen placement may experience acute pain due to tissue trauma from invasive procedures. Untreated pain can reduce comfort, interfere with activities, and slow the recovery process. Non-pharmacological interventions such as deep breathing relaxation and distraction (including imaginative distraction) can help reduce pain intensity through physical relaxation and diverting the patient's focus of attention. Objective: To determine the effect of deep breathing relaxation and distraction (including imaginative distraction) on reducing pain intensity using the Visual Analog Scale (VAS) in CAPD patients after double lumen placement. Methods: The research method used was a case report with a case study approach involving one patient undergoing Continuous Ambulatory Peritoneal Dialysis (CAPD) who experienced acute pain after double lumen insertion. Nursing interventions in the form of deep breathing relaxation and distraction techniques (music, conversation, and guided imagery distraction) were administered for one week according to the patient’s condition. Pain evaluation was conducted using the Visual Analog Scale (VAS) and observation of nonverbal responses before and after the intervention to assess changes in pain intensity and the patient’s response to the interventions provided. Results: At the initial measurement, the patient experienced VAS pain of 5–6 (moderate pain) accompanied by grimacing and a protective attitude. After 1 weeks of intervention, pain decreased to VAS 1–2 (mild pain). The patient appeared more relaxed, had improved facial expression, and was able to perform light activities. Imaginary distraction helped the patient shift focus from pain by imagining a calm and pleasant environment. Conclusion: Deep breathing relaxation and distraction (including imaginative distraction) effectively reduced pain intensity based on the VAS in patients with CAPD after double-lumen placement, thus it can be used as a supportive non-pharmacological therapy in nursing care.